A Contrastive Study of Arabic and Persian Formulas Against the Evil Eye used by Women - Ana Ramajo Cuesta (2015)
In Islamic societies, there exists the belief that a compliment can attract the'evil eye' unless it's accompanied by expressions that invoke God's protection. The purpose of this research is to analyze the use of these expressions and to conduct a contrastive study of Arabic and Persian formulas against the evil eye. In this research, the importance of these expressions and the use of courtesy formulas in responses to compliments about appearance and possessions are analyzed. Participants of the research are: 10 female native speakers of Arabic (between 19 and 24 years old) and 10 female native speakers of Persian (between 27 and 40 years old). Women were chosen in the study as they use more frequently formulas that invoke God's protection. All of them claimed to believe in the evil eye. Participants are requested to view two short videos in which the characters are talking about their appearance and possessions. Once they watch the videos, they recreate the dialogues in their own languages. The researchers analyze the use of formulas against the evil eye and the compliments responses and conduct a comparative study of the use of these formulas in Arabic and Persian.